Historical periods: the stigmatization of menstruation through various cultures and eras - Matthews, Emilie, author; Heineman, Kristin, advisor; Centelles, Vanessa, committee member (Colorado State University. Libraries, 2025)
The stigmatization of menstruation is a common occurrence throughout history and across the globe. Whereas modern-day menstrual stigmatization is evident through the use of euphemisms like "time of the month" and the seemingly inherent embarrassment and disgust associated with menstruation, this phenomenon can be achieved through a variety of methods. Using Link and Phelan's (2001) definition of stigma, this thesis examines the menstrual practices and beliefs of different cultures throughout history and explores whether menstruation was stigmatized in each instance. Analyzing evidence from the Roman Republic, various indigenous tribes from southeastern North America, the historic "Western" world, the Akan of Ghana, and modern-day India and Nepal, this paper demonstrates that menstrual stigmatization is evident both throughout history and the modern-world.
Keywords: menstruation; stigma; stigmatization